Acacia catechu Willd. and Acacia arabica Willd. decrease the extent of anxiety behavior by reducing oxidative stress and moderating neurochemicals. (10th August 2023) - Jyoti; Garg, Vandana
Abstract: Ethnopharmacological relevance: Anxiety is a very common psychiatric problem. It affects a large group of people in the world population. Acacia genus is well known for phenolic and flavonoid content. Literature showed its potential for various biological activities and is useful in the treatment of chest pain, asthma, bronchitis, wounds, mouth ulcer, colic, vitiligo, sore throat, inflammation, diarrhoea and also used as tonic. Aim of the study: The present study was conducted to assess the antianxiety potential of two plants Acacia catechu Willd. and Acacia arabica Willd. from the common family Fabaceae. Materials and methods: The stems of both plants were used for this purpose. Plants were subjected to complete exhaustive successive extraction using petroleum ether, chloroform, ethanol, and water as solvent. After pharmacognostic and phytochemical investigation, antianxiety activity was conducted on Swiss albino mice at different dose levels (100, 200, 300, & 400 mg/kg body weight p.o.) for all successive extracts of both plants. Two active extracts from each plant were further assessed for anxiolytic potential using the open-field test and mirror chamber test. One extract with the maximum response from each plant was further screened using mCPP-induced anxiety test. Results: The stem of ethanol extract of A. catechu showed comparable antianxiety activity at 400 mg/kg to the standard drug diazepam (2.5 mg/kg). Improved SOD, catalase, and LPO levels were noted after administration of A. catechu ethanolic extract at 400 mg/kg. Conclusions: In conclusion, A. catechu ethanolic extract improved anxiety symptoms at dose-dependent levels in mice. Graphical abstract: Image 1 Highlights: Extraction of stems of Acacia catechu Willd. and Acacia arabica Willd. using petroleum ether, chloroform, ethanol and water. Screening of behavioral parameters of all extracts using elevated plus maze and light dark test. Two active extracts of each plant evaluated for anxiolytic potential using mirror chamber test and open-field test. One most active extract of each plant further tested using meta-chlorophenylpiperazine (mCPP) induced anxiety test. Acacia catechu Willd. extract showed maximum anti-anxiety activity.